Fit-for-purpose modelling of radiocaesium soil-to-plant transfer for nuclear emergencies: a review. (May 2019) - Almahayni, Talal; Beresford, Nicholas A.; Crout, Neil M.J.; Sweeck, Lieve
Abstract: Numerous radioecological models have been developed to predict radionuclides transfer from contaminated soils to the food chain, which is an essential step in preparing and responding to nuclear emergencies. However, the lessons learned from applying these models to predict radiocaesium (RCs) soil-to-plant transfer following the Fukushima accident in 2011 renewed interest in RCs transfer modelling. To help guide and prioritise further research in relation to modelling RCs transfer in terrestrial environments, we reviewed existing models focussing on transfer to food crops and animal fodders. To facilitate the review process, we categorised existing RCs soil-to-plant transfer models into empirical, semi-mechanistic and mechanistic, though several models cross the boundaries between these categories. The empirical approach predicts RCs transfer to plants based on total RCs concentration in soil and an empirical transfer factor. The semi-mechanistic approach takes into account the influence of soil characteristics such as clay and exchangeable potassium content on RCs transfer. It also uses ʻbioavailableʼ rather than total RCs in soil. The mechanistic approach considers the physical and chemical processes that control RCs distribution and uptake in soil-plant systems including transport in the root zone and root absorption kinetics. Each of these modelling approaches has its advantages and disadvantages. The empirical approach is simple and requires two inputs, but it is often associated with considerably uncertainty due to the large variability in the transfer factor. The semi-mechanistic approach factorises more soil and plant parameters than the empirical approach; therefore, it is applicable to a wider range of environmental conditions. The mechanistic approach is instrumental in understanding RCs mobility and transfer in soil-plant systems; it also helps to identify influential soil and plant parameters. However, the comlexity and the large amount of specific parameters make this approach impractical for nuclear emergency preparedness and response purposes. We propose that the semi-mechanistic approach is sufficiently robust and practical, hence more fit for the purpose of planning and responding to nuclear emergencies compared with the empirical and mechanistic approaches. We recommend further work to extend the applicability of the semi-mechanistic approach to a wide range of plants and soils. Highlights: We reviewed main radicaesium soil-to-plant transfer models. We recommend semi-mechanistic models for emergency planning. We propose actions to improve model performance and parameter database.